The Milk Street cookbook : the definitive guide to the new home cooking, with every recipe from the TV show, 2017-2025 - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Yanagihara, Dawn; Smolin, Ari; Martin, Wes; Hill, Courtney; Borges, Bianca; Card, Matthew; Hattabough, Rose (Voracious, Little, Brown and Company, 2024)
"...Featuring more than 620 tried-and-true recipes, including every recipe from every episode of the TV show, this book is the ultimate guide to high-quality, low-effort cooking--the perfect kitchen companion for cooks of al skill levels."--